1991
DOI: 10.1056/nejm199108293250901
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Transmission of Human Immunodeficiency Virus Type 1 from Mother to Infant

Abstract: HIV-1 infection can be transmitted from mothers to infants during the postnatal period. Colostrum and breast milk may be efficient routes for the transmission of HIV-1 from recently infected mothers to their infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
76
0
8

Year Published

1992
1992
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(84 citation statements)
references
References 16 publications
0
76
0
8
Order By: Relevance
“…Dean et al (1988) and Mundy et al (1987) reported none or low level of pathogens in urine, sweat, breast milk, branchoalvolar lavage fluid, amniotic fluid, synovial fluid, faeces and tears which were not thought to be important source in virus transmission (Fujikawa et al, 1985), but this assumption has also changed with the report of Groopman and Greenspan (1996); Amory et al (1992); Scarlatti (1996); van da Perre et al (1991). Though not a natural source of HIV transmission, cerebrospinal fluid (CSF) in neurologic patients have been shown to contain large amount of virus when compared to other body fluids (Hollander and Levy, 1987;Ho et al, 1989).…”
Section: Parental Saliva and Other Body Fluidsmentioning
confidence: 99%
“…Dean et al (1988) and Mundy et al (1987) reported none or low level of pathogens in urine, sweat, breast milk, branchoalvolar lavage fluid, amniotic fluid, synovial fluid, faeces and tears which were not thought to be important source in virus transmission (Fujikawa et al, 1985), but this assumption has also changed with the report of Groopman and Greenspan (1996); Amory et al (1992); Scarlatti (1996); van da Perre et al (1991). Though not a natural source of HIV transmission, cerebrospinal fluid (CSF) in neurologic patients have been shown to contain large amount of virus when compared to other body fluids (Hollander and Levy, 1987;Ho et al, 1989).…”
Section: Parental Saliva and Other Body Fluidsmentioning
confidence: 99%
“…Evidence for transmission of HIV through breastfeeding is based on instances where mothers have developed HIV infection postnatally either through a blood transfusion [49] or presumed sexual intercourse [33,501 and their infants have subsequently shown infection. What is not clear is the proportion of mothers infected prenatally, whose infants have not been infected during pregnancy or delivery, who may infect their infants through breast-feeding.…”
Section: Breast-feedingmentioning
confidence: 99%
“…The pairs designated 10, 12 and 16 in the reports of van de Perre et al (1991van de Perre et al ( , 1992 correspond to 538, 566 and 564 in this study. Children 538 and 566 seroconverted within the same 3 month period as did their mothers, suggesting vertical transmission during the acute phase of maternal infection (van de Perre et al, 1991). Child 564 seroconverted 18 months after maternal seroconversion (van de Perre et al, 1992).…”
mentioning
confidence: 99%
“…The women seroconverted after childbirth and their children became infected through breast milk. The design of the cohort study and details of serological and diagnostic PCR data are given elsewhere (van de Perre et al, 1991(van de Perre et al, , 1992. The pairs designated 10, 12 and 16 in the reports of van de Perre et al (1991van de Perre et al ( , 1992 correspond to 538, 566 and 564 in this study.…”
mentioning
confidence: 99%
See 1 more Smart Citation